Compressibility characteristics of compacted clay treated with cement, peat ash and silica sand - Mousavi, Seyedesmaeil; Leong, Sing Wong (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper investigates the compressibility characteristics of compacted clay treated with cement, peat ash and silica sand. For this purpose, one dimensional consolidation tests were conducted to determine the soil consolidation properties. The test specimens were trimmed from the compaction test specimen. The 1D consolidation test specimen was subjected to the normal pressures of 2.5, 5, 10, 20, 40, 80 and 160 kPa in sequence on the test specimen which was saturated with distilled water. At the end of the loading period of 80 kPa, the vertical load was removed and the specimen was allowed to expand for 24 h for the purpose of evaluating of its swelling behavior. The results showed that void ratio of the soil specimens decreased with increasing effective normal pressure. The laboratory investigation clearly demonstrates that, settlement is as the compression of a soil specimen due to vertical loading applied at the top surface of the 1D consolidation test specimen. It was concluded that, the compression settlement of the stabilized soil with the binder composition of 18% cement, 2% peat ash and 5% silica sand improved by almost 1.3-fold. A notable discovery is the suitability of the stabilized soil for road embankment and low lying marginal area for foundation works; also solving the environmental problems in relation to peaty ground. However, sufficient laboratory and field testing are required.